Critical Reflections on The Legal Science - Dewi Setyowati (Fakultas Hukum Universitas Mataram, 2019)
Generally, there are two opposing sides when discussing the epistemology of the law, namely realist and anti-realist. The point of difference between the two sides includes several topics responding to the basic topics related to the definition, scope, methodology and truth that want to be achieved by the science of law. This research aims are to answer some of the epistemological problems of jurisprudence and what philosophical assumptions based on and methodological implications for achieving truth in realist and anti-realist tensions. This article uses a conceptual review of the epistemic study of law. The result of this research is that the epistemology discourse of jurisprudence has been a topic of debate for a long time and stems from tensions between rationalism, empiricism, and pragmatism. Methodological differences also have logical consequences for the attainment of the truth that realists and anti-realists aim to address. Correspondence becomes the truth to be achieved by law according to the realist. In contrast to the belief of anti-realists who believe that the truth is not just a statement, but it becomes true if it fits and supports with other statements. Whereas pragmatic assumes the validity of the law is measured by its validity at its usefulness.